2021
DOI: 10.1111/cas.14813
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 is a key factor for tamoxifen resistance and has the potential to predict the efficacy of CDK4/6 inhibitors in breast cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…In contrast, another study showed that miR-129-5p enhances the sensitivity of breast cancer cells to paclitaxel by inhibiting autophagy and HMGB1, thereby increasing apoptosis [ 79 ]. In addition, patients with endocrine therapy (ET)-refractory HR-positive breast cancer showed greater HMGB1 expression correlated with worse postoperative progression-free survival (PFS) [ 80 ]. Among patients with ET-resistant disease, treatment with cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors benefitted the PFS of HMGB1-positive patients relative to that of HMGB1-negative patients [ 80 ].…”
Section: Roles Of Damps and Icd In The Clinical Significance Of Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, another study showed that miR-129-5p enhances the sensitivity of breast cancer cells to paclitaxel by inhibiting autophagy and HMGB1, thereby increasing apoptosis [ 79 ]. In addition, patients with endocrine therapy (ET)-refractory HR-positive breast cancer showed greater HMGB1 expression correlated with worse postoperative progression-free survival (PFS) [ 80 ]. Among patients with ET-resistant disease, treatment with cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors benefitted the PFS of HMGB1-positive patients relative to that of HMGB1-negative patients [ 80 ].…”
Section: Roles Of Damps and Icd In The Clinical Significance Of Breast Cancermentioning
confidence: 99%
“…In addition, patients with endocrine therapy (ET)-refractory HR-positive breast cancer showed greater HMGB1 expression correlated with worse postoperative progression-free survival (PFS) [ 80 ]. Among patients with ET-resistant disease, treatment with cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors benefitted the PFS of HMGB1-positive patients relative to that of HMGB1-negative patients [ 80 ]. HMGB1 promotes tamoxifen resistance via TLR4, resulting in the activation of the NF-κB signaling pathway, which is restored by CDK4/6 inhibitors [ 80 ].…”
Section: Roles Of Damps and Icd In The Clinical Significance Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC4 was also reported to promote OS cell proliferation and invasion (38). High mobility group box-1 (HMGB1) is highly expressed in a number of tumors, including lung, breast, head and neck, nasopharyngeal and colorectal cancer, indicating that it may be associated with the occurrence, invasion and metastasis of tumors (39)(40)(41)(42)(43).…”
Section: Circ-lrp6 Contributes To Osteosarcoma Progression By Regulat...mentioning
confidence: 99%
“…These DAMPs induced by chemotherapeutic drugs could promote a state of anti-tumor immunity. However, other studies showed that DAMPs such as HMGB1, CRT, and ATP were also involved in BC progression, metastasis, and drug resistance ( 55 57 ). So, DAMPs represent a double-edged sword in BC.…”
Section: Enhancing the Antigenicity Or Adjuvanticity Of Bc Cellsmentioning
confidence: 99%